A process and kit for isolation and purifying biology materials. - Abdul Rahim, Raha; Yiap, Beow Chin (2004)

(untitled)
The present invention relates to a process and kit useful for isolating and purifying biological materials. The process according to the present invention can be used to isolate nucleic acids or protein from a wide range of organisms across the various kingdoms. The process involving basically 3 steps namely lysis, clean-up and harvest, 3 solutions comprising 6 chemicals and a single changing of sample tube. The process offers a numbers of advantages including fast, high yield, good quality and purity products, flexible in scaling, environmental friendly, low cost and easier to perform.